Micro Hydropower System Design for Gua Kelam Electricity Supply - Mamoud A. M. Albreem; Rosnita Md Aspan (International Journal of Applied Power Engineering (IJAPE), 2018)
Sufficient and uninterrupted electricity supply is one of the main factors to develop the country. Today, electricity can be generated using a variety of sources, whether from non-renewable sources as well as renewable resources. To generate electrical power, Malaysia can't rely entirely on non-renewable resources such as petroleum and coal as these are finite resources which are experiencing depletion around the world. Electricity generated from renewable sources such as water, particularly from micro hydropower systems is considered the cheapest and most environmentally friendly source of electrical energy. Based on the reconnaissance study conducted, the streams of flowing water in Gua Kelam have the potential to yield about 34.29 kW of electricity power, based on the head height of 27 m and flow rate 0.216 m3/s. In this paper, a model for an ordinary micro hydropower facility has been proposed. It links various electromechanical equipment consisting of a hydraulic turbine governor, and a synchronous generator. The modeling was executed to design a micro hydropower system as an alternative source of supply of electricity to Gua Kelam, Perlis. The proposed model was tested by placing a three-phase fault to earth for the purpose of testing the reliability of the system. With the selection of an appropriate control system, the proposed model is very suitable for the development of micro hydropower system at a potential site such as Gua Kelam.